Bridging Social Innovation and Social Work: Balancing Science, Values, and Speed. (March 2017) - Halvorsen, Cal J.
This article highlights how the social work academy can support innovative research, dissemination, and implementation and is a response to and extension of arguments made by Dr. Marilyn L. Flynn on innovation in social work. It argues that social work researchers need to strike a balance between the often slow and methodical scientific research community and the often rapid and reactive social innovation community to best respond to societal needs. From an emerging scholar's point of view, it concludes by emphasizing how shifting priorities in social work tenure and promotion processes can broaden the impact of social work research.